Estudos fitoquímico e biológico de Helicteres velutina K. Schum (Sterculiaceae) nos estágios de desenvolvimento do Aedes aegypti L. (Diptera: Culicidae) - Fernandes, Diégina Araújo (2021)
Aedes aegypti is the vector of emerging and neglected diseases, such as dengue, chikungunya and zika. Helicteres velutina popularly known as 'pitó', is an endemic plant in Brazil, traditionally used by an indigenous tribe Pankararé/Raso da Catarina/Bahia, as an insect repellent. The present study aimed to isolate the phytochemicals of the species H. velutina and evaluate its insecticidal and repellent potential against Ae. aegypti. The crude ethanolic extract (CEE) from aerial parts of H. velutina was subjected to liquid liquid chromatography with hexane, dichloromethane, ethyl acetate and n-butanol, obtaining its respective phases. A biological screening of these phases against the stages of the mosquito's life cycle was carried out. The viability of the eggs was evaluated using different concentrations of the test substances for 25 days, the survival of larvae, pupae and adults was verified after 48 and 72 hours. The phytochemical study of promising in vitro phases was carried out using classic and hyphenated chromatographic techniques, in addition to spectroscopic methods (1D/2D NMR, IR and LCMS), resulting in the isolation and identification of twelve chemical constituents, including two sulphated flavoinoids unpublished in the literature (mariahine and condadine). The isolated molecules of this species were subjected to in silico screening, using applicability domain and molecular docking with vector target proteins (1YIY, 1PZ4 and 3UQI), the substances most likely to be bound, were tested in vitro against Ae. aegypti larvae. The repellency of the extract, phases and substances was evaluated with a Y-tube olfactometer. Cytotoxic activity was assessed using fluorescence microscopy and propidium iodide staining, evaluating the production of hemocytes and nitrous oxide concentration. The biological screening showed that the hexane and dichloromethane phases showed better results, causing 72.7% and 67.7% of eggs to become unviable; LC50 of 3.88 and 5.80 mg/mL for larvae; 0.12 mg/mL and 8.85 mg/mL for pupae; 8.01 mg/mL and 0.74 mg/mL for adults (tarsal test), 0.05 mg/mL and 0.23 mg/mL (body test), respectively. Tiliroside and 7,4'-di-O-methyl-8-O-sulphate flavone showed larvicidal activity, with LC50 of 0.275 mg/mL after 72 h and 0.182 mg/mL after 24 h of exposure, respectively. The dichloromethane phase and the 7,4'-di-O-methyl-8-O-sulphate flavone were more promising, observing the presence of plasmocytes, suggesting that these would be the responsible hemocytes by the greater production of nitric oxide in the treated larvae, acting as a defense agent. This is the first report of sulphated flavonoids in the Sterculiaceae family, it was also possible to prove that the presence of the sulphate group (OSO3H) at C-8 was crucial in larvicidal activity. These findings provide a better understanding of the insecticidal and repellent activity of H. velutina against Ae. aegypti data that allow us to glimpse the development of a natural product that is more effective in combating the vector than allopathic repellents.